The removal of Pb (II) and Cd (II) with hydrous manganese dioxide: mechanism on zeta potential and adsorption behavior. Issue 24 (27th October 2020) - Wu, Shanshan; Xie, Fencun; Chen, Sijie; Fu, Binbin
ABSTRACT: In this study, the removal of Pb (II) and Cd (II) in aqueous solution by employing hydrous manganese dioxide (HMO) is investigated. The HMO synthesized was characterized by SEM, XRD, BET, FT-IR, and XPS. Simultaneously, the effect of Zeta potential (ZP), solution pH and contact time were discussed. The results reveal that at pH 5.0, 1-HMO (−51.7 mV) with the highest |ZP| value can reach equilibrium and reach 95.7% removal rate within 30 mins. The isotherm and kinetic data fitted Langmuir and pseudo-second-order models well. The maximum adsorption capacities calculated by Langmuir equation are 475.4 mg/g for Pb (II) and 140.3 mg/g for Cd (II) at 303.15 K, respectively. The binary experiment indicates the HMO showed a better affinity for Pb (II) than Cd (II). Thermodynamic studies (ΔG < 0, ΔH > 0, ΔS > 0) implies the both adsorptions are endothermic and spontaneous process. The intraparticle model analysis indicates that the film discussion controls the metal ions adsorption at the earlier stage and the intraparticle diffusion at the middle stage, while a chemical bonding process at the equilibrium stage. The FTIR and XPS analysis further proves Pb (II) and Cd (II) being adsorbed onto the surface of HMO as Pb-O and Cd-O, resulting from ion exchange and complexation. The reacted HMO could be recycled and reused for several times in a high efficiency above 90% by adding HCl or new HMO adsorbent. Simple preparation, low cost and remarkable removal efficiency make HMO a promising material in the treatment of heavy metal-contaminated water. GRAPHICAL ABSTRACT: UF0001